Evaluation of muscle strength and manual dexterity in patients with Charcot-Marie-Tooth disease - Kobesova, Alena; Nyvltova, Marcela; Kraus, Josef; Kolar, Pavel; Sardina, Angela; Mazanec, Radim; Andel, Ross (Journal of hand therapy, 2016)
STUDY DESIGN: Matched pair study. INTRODUCTION: Differences in hand-muscle strength/dexterity between dominant (DH) and non-dominant (NDH) hand in Charcot-Marie-Tooth disease (CMT) are not well understood. PURPOSE OF THE STUDY: To compare muscle strength/dexterity between DH and NDH and to correlate manual dexterity, strength and sensory function. PATIENTS AND METHODS: Thirty CMT patients were studied using functional muscle testing (FMT) and strength (dynamometry), dexterity (the Nine Hole Peg Test [NHPT]), and Jebsen-Taylor Hand Function [JTT]), and sensory function (the Nottingham Sensory Assessment [NSA]). RESULTS: Scores were worse for DH than NDH on FMT (p = 0.043) and NHPT (p = 0.014) but not on JTT (p = 0.098), handgrip strength (p = 0.710) or tripod pinch (p = 0.645). NSA did not correlate significantly with any tests (p's0.05). CONCLUSIONS: In CMT disease, DH appears more impaired than NDH in terms of function and dexterity. Greater muscle weakness in DH may also emerge as CMT progresses. LEVEL OF EVIDENCE: 3b.
Keywords: Humans; Functional Laterality; Hand strength; lidé středního věku; Charcot-Marie-Tooth disease; Hand Strength; Female; Aged; mladý dospělý; dospělí; senioři; lidé; Neurologic Examination; Charcotova-Marieova-Toothova nemoc; neurologické vyšetření; Adult; Muscle Strength Dynamometer; síla ruky; ženské pohlaví; funkční lateralita; Male; Middle Aged; Charcot-Marie-Tooth Disease; svalová síla - dynamometr; motorické dovednosti; Young Adult; Manual dexterity; mužské pohlaví; Motor Skills; Sensory function; Hereditary motor and sensory neuropathy